Effectiveness of smart health-based rehabilitation on patients with poststroke dysphagia: A brief research report - Zhang, Jian-Rong; Wu, Yu-E; Huang, Yan-Fang; Zhang, Shu-Qing; Pan, Wen-Li; Huang, Jin-Xia; Huang, Qing-Ping (Frontiers in Neurology, 2023)
Objective This study aimed to evaluate the effectiveness of smart health-based rehabilitation on patients with poststroke dysphagia (PSD). Methods We recruited 60 PSD patients and randomly allocated them to the intervention (n = 30) and control (n = 30) groups. The former received the smart health-based rehabilitation for 12 weeks, whereas the latter received routine rehabilitation. Water swallow test (WST), standardized swallowing assessment (SSA), swallow quality-of-life questionnaire (SWAL-QOL), stroke self-efficacy questionnaire (SSEQ), perceived social support scale (PSSS) and nutritional measurements including body weight, triceps skinfold thickness (TSF), total protein (TP), serum albumin (ALB) and serum prealbumin (PA) in both groups were measured. Results When the baseline WST, SSA, SWAL-QOL, SSEQ, PSSS and nutritional measurements were examined, there was no significant difference between the intervention group and the control group (P > 0.05). After rehabilitation interventions, the WST and SSA scores in the intervention group were significantly lower than those in the control group (P < 0.01). The SWAL-QOL, SSEQ and PSSS scores in the intervention group were significantly higher than in the control group (P < 0.01). Compared with the control group, the intervention group showed an increase in the serum levels of PA (P < 0.01). However, no statistically significant difference existed between the intervention group and the control group in terms of body weight, TSF, TP or ALB (P > 0.05). Conclusions Overall, our data revealed that smart health-based rehabilitation is significantly beneficial to the swallowing function, quality of life, self-efficacy, and social support for PSD patients when compared with routine rehabilitation. However, nutritional measurements were not significantly improved in such patients under the smart health-based rehabilitation when compared the routine rehabilitation. In the future, it is necessary to extend the intervention time to further evaluate the long-term efficacy of smart health-based rehabilitation on nutritional measurements of PSD patients.